Smoking Status, Body Mass Index, Health-Related Quality of Life, and Acceptance of Life With Illness in Stable Outpatients With COPD - Wytrychiewicz, Kinga; Pankowski, Daniel; Janowski, Konrad; Bargiel-Matusiewicz, Kamilla; Dąbrowski, Jacek; Fal, Andrzej M. (Frontiers in Psychology, 2019)
Both smoking and obesity are important factors related to the etiology and clinical features of chronic obstructive pulmonary disease (COPD). The aim of this study was to carry out a deeper analyses of the links between smoking status and body mass index on one hand and individual dimensions of health – related quality of life and acceptance of life with disease in patients with COPD. Information about BMI, smoking status, clinical features of COPD, a COPD assessment test, and airflow obstruction indicators were obtained from 105 outpatients attending a pulmonary clinic. Analysis of covariance demonstrated that the subgroups of patients distinguished due to the smoking status and BMI differed significantly in severity of Cough, Dyspnea, Limitation of daily activities, Lack of self – confidence and Quality of sleep, independently of sociodemographic and clinical features of COPD. The results of our study suggest a certain path of the potential effects of obesity and smoking status on quality of life. Risky health behaviors such as smoking and at-risk body mass exert effect only on some aspects of health-related quality of life.